EFFECTIVENESS OF BINTARO (Cerberra odollam Gaertn.) LEAF ETHANOLIC EXTRACT AGAINST Staphylococcus aureus IN-VITRO BIOFILM FORMATION - Filania S. Kanja; Lisa Soegianto; Sumi Wijaya (UNEJ e-Proceeding)
Biofilm is a structural form of a group ofmicroorganisms protected by matrik extracellularcalled Extracellular Polymeric Substance (EPS),where EPS is a product produced by thesemicroorganisms itself and as a shelter from thebad influence in environment. The structure ofthese matrix is strings which cross each otherwhich can be adhesive for biofilm4).Biofilm from Staphylococcus aureus seen inchronicle infection cases as ulcer on diabeticsfoot, venous statis ulcer and pressure sores.Patients with infection wound with chronicleulcer in vein feet found positive culture ofStaphylococcus aureus as much as 88-93,3% froma number of infection found.Figure 1. Cerberra odollam Gaertn.Bintaro can be used as an analgesic,anticonvulsant, kardiotonik and antihypertensive2).The aim of this study is to test the effectivenessof the ethanol extracts of bintaro leaves (Cerberraodollam Gaertn.) towards the Staphylococcusaureus formation by in vitro.MATERIALSBintaro leaves (Cerberra odollam Gaertn.),Staphylococcus aureus culture ATCC 6538, petridish, ose wire , micro pipet, autoclave (AllAmerican Model No 25x, USA), incubator(Memmert and Binder, Germany), Laminar AirFlow (LAF) (Type V-130, Indonesia), microplate,microplate reader (Thermofisher Scientific,America), vacuum rotary evaporator (BÜCHI,Germany), weight analytic (Sartorius TE 214 S,Germany), oven (Memmert, Germany).